A Thermally Populated, Perpendicularly Twisted Alkene Triplet Diradical. Issue 47 (20th October 2016) - Wentrup, Curt; Regimbald‐Krnel, Michèle J.; Müller, Dennis; Comba, Peter
Abstract: Variable‐temperature NMR and ESR spectroscopic studies reveal that bis(dibenzo[a, i]fluorenylidene) 1 possesses a singlet ground state, 1 (S0 ), while the 90° twisted triplet 1 (T1 ) is populated to a small extent already at room temperature. Analysis of the increasing amount of paramagnetic 1 (T1 ) at temperatures between 300 and 500 K yields the exchange interaction J ex / h c =3351 cm −1 and a singlet–triplet energy splitting of 9.6 kcal mol −1, which is in excellent agreement with calculations (9.3 kcal mol −1 at the UKS BP86/B3LYP/revPBE level of theory). In contrast, the zero‐field splitting parameter D is very small (calculated value −0.018 cm −1 ) and unmeasurable. Abstract : Twist of fate : Bis(dibenzo[ a, i ]fluorenylidene) (see scheme) has a closed‐shell singlet ground state, but the amount of the 90° twisted, antiferromagnetic triplet diradical increases in the temperature range 300–500 K. The exchange coupling J ex / h c was determined to be 3551 cm −1, which corresponds to a singlet–triplet energy splitting of 9.6 kcal mol −1 .